The Contributions of Letter Features to Arabic Letter Knowledge for Arabic-Speaking Kindergartners. (3rd September 2022) - Tibi, Sana; Edwards, Ashley A.; Kim, Young-Suk Grace; Schatschneider, Christopher; Boudelaa, Sami
ABSTRACT: Studies have suggested that multiple features influence letter knowledge across different orthographies. Arabic offers a unique opportunity to investigate the relations of letter properties on letter knowledge, but research on Arabic letter knowledge is scarce. This study was designed to investigate (a) letter frequency, (b) letter sequence, (c) visual similarity, (d) developmental stage of the phonemes of the letters, and (e) diglossia as possible factors that contribute to Arabic letter knowledge. A total of 142 (Mean age = 67 months) native Arabic-speaking monolingual kindergartners were administered a letter knowledge task. Data were analyzed using Cross-Classified Generalized Random-Effects analysis, which allows partitioning of variance into that due to persons and due to letters to provide a more unbiased estimate of item-level variance. Results showed that letter frequency, late developing sounds, and diglossia were statistically significant when each was entered separately in a model whereas visual similarity and letter sequence were not. However, when all letter features were entered simultaneously, letter frequency was the only feature that contributed significantly to the prediction of Arabic letter knowledge. The present study underscores the important role of letter frequency in Arabic letter knowledge. Implications for assessment and instruction are discussed.